Multidimensional diffusion processes - Stroock Daniel W; Varadhan S R Srinivasa (Berlin Springer-Verlag, 1979)
This book is an excellent presentation of the application of martingale theory to the theory of Markov processes, especially multidimensional diffusions. This approach was initiated by Stroock and Varadhan in their famous papers. (...) The proofs and tec
Keywords: Diffusion processes; Probabilities